Engineering materials science - Ohring, Milton, 1936- (Academic Press, 1995)
Milton Ohring's Engineering Materials Science integrates the scientific nature and modern applications of all classes of engineering materials. This comprehensive, introductory textbook will provide undergraduate engineering students with the fundamental background needed to understand the science of structure-property relationships, as well as address the engineering concerns of materials selection in design, processing materials into useful products, andhow material degrade and fail in service. Specific topics include: physical and electronic structure; thermodynamics and kinetics; processin.